Penentuan Pola Penjualan Obat Menggunakan Algoritma Apriori - Aldo Aprilio Arifin; Husdi; Yusrianto Malago (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2023)
Piramid Mulia Pharmacy is a health facility where a place to sell drugs and concoct drugs based on a doctor's prescription, as well as trade medical goods. Piramid Mulia Pharmacy is still difficult in analyzing drug sales, because there is no system to analyze. The results showed that the Drug Sales Pattern Determination System Using the Apriori Algorithm has met the requirements of programming logic and is not complex, where CC = V (G) = 4 based on White Box testing, then the system has been free from various component errors based on Black Box testing. Thus, an efficient Drug Sales Pattern Determination System using the Apriori Algorithm is obtained so that it can be implemented.